Teaching Factory Model as an Innovative Educational Approach to Enhance Competence Development in Hospitality: A Case Study at de Balen Soultan Hotel - Gumilar, Gugung; Ridwan, Masri (EduLine: Journal of Education and Learning Innovation, 2024)
This study investigates the impact of the Teaching Factory model on the development of student competencies in the hospitality sector at de Balen Soultan Hotel. Despite the growing importance of practical skills in the industry, gaps remain in the effectiveness of current educational approaches. To address this issue, the research employs a quantitative method using Multiple Linear Regression analysis via IBM SPSS 25 software to evaluate the relationship between the implementation of the Teaching Factory model (independent variable) and waiter competencies (dependent variable). Data were collected from 74 students enrolled in the Lombok Tourism Polytechnic catering program, utilizing a purposive sampling technique. The findings reveal a strong positive correlation (0.850) between the Teaching Factory model and student competencies, indicating that the model significantly enhances students’ preparedness for industry demands. The study concludes that implementing the Teaching Factory model is crucial for equipping students with essential skills, thereby fostering their success in the hospitality sector. It recommends further integration of industry practices into vocational training programs to improve student outcomes and enhance their employability